Clonal hematopoiesis of indeterminate potential and type 2 diabetes mellitus among patients with STEMI: from a prospective cohort study combing bidirectional Mendelian randomization - Xiaoxiao Zhao; Jiannan Li; Shaodi Yan; Yu Tan; Runzhen Chen; Nan Li; Jinying Zhou; Chen Liu; Peng Zhou; Yi Chen; Hongbing Yan; Hanjun Zhao; et al. (Cardiovascular Diabetology)
Abstract Aim Both clonal hematopoiesis of indeterminate potential (CHIP) and type 2 diabetes mellitus (T2DM) are conditions closely associated with advancing age. This study delves into the possible implications and prognostic significance of CHIP and T2DM in patients diagnosed with ST-segment elevation myocardial infarction (STEMI). Methods Deep-targeted sequencing employing a unique molecular identifier (UMI) for the analysis of 42 CHIP mutations—achieving an impressive mean depth of coverage at 1000 × —was conducted on a cohort of 1430 patients diagnosed with acute myocardial infarction (473 patients with T2DM and 930 non-DM subjects). Variant allele fraction ≥ 2.0% indicated the presence of CHIP mutations. The association between CHIP and T2DM was evaluated by the comparison of (i) the prevalence of CHIP mutations among individuals with diabetes versus those without, (ii) the clinical characteristics delineated by CHIP mutations within the cohort of diabetic patients and (iii) the prognostic significance and correlation of CHIP mutations with mortality rates in T2DM subjects. Furthermore, a two-sample bidirectional Mendelian randomization study was performed using genetic instruments from the genome-wide association study for TET2 mutation CH from the UK Biobank (UKB) (2041 cases,173,918 controls) to investigate the causal relationship with T2DM from the FinnGen consortium (65,085 cases and 335,112 controls), and vice versa. Results (i) Most commonly CHIP mutations exhibiting a variant allele fraction of ≥ 2.0% were identified in 50/473 (10.6%) patients with T2DM, demonstrating a greater prevalence compared to non-DM subjects [69/930 (7.4%); P < 0.05] across various age groups. (ii) After multivariable adjustment, the mortality of any CHIP mutations were 2.03-fold higher in DM [adjusted hazard ratio (HR) 2.03; 95% confidence interval (CI) 1.07–3.84, P < 0.05]. (iii) In gene-specific analyses, TET2 somatic mutation presented the highest association with mortality among T2DM (adjusted HR 5.24; 95% CI 2.02–13.61, P = 0.001). ASXL1 CHIP mutation which displayed a striking correlation with cardiac death (HR: 3.14; 95% CI 1.24–7.93; P < 0.05) with consistent associations observed among T2DM subgroup (HR: 4.51; 95% CI 1.30–15.6; P < 0.05). (iv) The correlation between PCSK9 and the Tet2-CHIP mutation was observed in both the T2DM cohort (correlation = 0.1215, P = 0.011) and the overall enrolled cohort (correlation = 0.0578, P = 0.0382). (v) Bidirectional Mendelian randomization studies indicated that the development of T2DM increases the propensity for CHIP. However, CHIP does not subsequently accelerate the onset of T2DM. Conclusion CHIP mutations, particularly TET2, are more prevalent in patients with T2DM compared to individuals without diabetes. The presence of these mutations is associated with adverse clinical outcomes, notably increased mortality rates. Moreover, bidirectional Mendelian randomization analyses provide supporting evidence for a potential causal relationship between TET2-related CHIP and the development of T2DM. Graphical abstract Central Illustration: The association between clonal hematopoiesis of indeterminate potential (CHIP) and type 2 diabetes mellitus (T2DM): The prevalence of CHIP is notably higher in individuals with T2DM, as demonstrated in a prospective study within an Asian cohort of acute myocardial infarction (AMI). Furthermore, the predictive value of CHIP as a marker for poor clinical prognosis in T2DM has been assessed in this study. Mendelian randomization studies suggest that the development of T2DM may increase the propensity for CHIP, as indicated by findings from the UK Biobank and FinnGen consortium. T2DM, type 2 diabetes mellitus; CHIP, clonal haematopoiesis of indeterminate potential.